2017
DOI: 10.1002/erv.2497
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ASD Traits on Treatment Outcomes of Eating Disorders in Girls

Abstract: Evidence links high levels of Autism Spectrum Disorder Traits in women with chronicity of anorexia nervosa. This study reports through clinical audit the impact of ASD traits on treatment outcomes of girls who were referred for treatment in a specialist eating disorder service. Presence of current, but not early childhood, ASD traits was elevated in comparison with previously reported community samples. Current ASD traits were correlated with emotional disorders and with need for treatment augmentation (psychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
61
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 31 publications
9
61
1
Order By: Relevance
“…The 15.4% (23/149) prevalence of SAS scores below cut-off (ASD traits group) in this sample is the same as that found in a clinical cohort of AN and EDNOS cases (Stewart et al, 2017). However, the computer generated probability of ASD diagnosis from the DAWBA in the clinical cohort (Stewart et al, 2017) did not differ from community norms, while in our sample, a trained psychiatrist reviewed the DAWBA and we found one probable and five possible cases (Rhind et al, 2014).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The 15.4% (23/149) prevalence of SAS scores below cut-off (ASD traits group) in this sample is the same as that found in a clinical cohort of AN and EDNOS cases (Stewart et al, 2017). However, the computer generated probability of ASD diagnosis from the DAWBA in the clinical cohort (Stewart et al, 2017) did not differ from community norms, while in our sample, a trained psychiatrist reviewed the DAWBA and we found one probable and five possible cases (Rhind et al, 2014).…”
Section: Discussionsupporting
confidence: 77%
“…The clinical cohort (Stewart et al, 2017) included people with an age range of 9-18 (mean 5 14.6), whereas the current study included people from age 13-21 years (mean 5 17). Previous studies suggest that the prevalence of ASD traits varies according to the age/duration of illness of the sample included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential mechanisms underlying the relationship between AN and autism could include shared cognitive traits: commonly with research in autism, literature shows that people with AN exhibit problems with rigidity, central coherence, and emotional and social processing that may persist following recovery (Harrison, Mountford, & Tchanturia, 2014;Lang, Lopez, Stahl, Tchanturia, & Treasure, 2014;Katie Lang et al, 2016;Leppanen, Sedgewick, Treasure, & Tchanturia, 2018;Westwood, Lawrence, Fleming, & Tchanturia, 2016;Westwood, Stahl, Mandy, & Tchanturia, 2016). Significantly, heightened autistic traits in people with AN are associated with more severe presentations and poorer treatment outcomes (Nielsen, Anckarsater, Gillberg, Rastam, & Wentz, 2015;Tchanturia, Adamson, Leppanen, & Westwood, 2017;Tchanturia, Larsson, & Adamson, 2016), leading to suggestions that traditional treatment approaches may need to be adapted for this population (Dudova, Kocourkova, & Koutek, 2015;Stewart, McEwen, Konstantellou, Eisler, & Simic, 2017;. Treasure, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, treatment could be exacerbated due to problems with patient‐therapist communication, deficits in metacognition, and emotional understanding (Grainger, Williams & Lind, ; Kinnaird, Norton & Tchanturia, ; Losh & Capps, ). Previous research on treatment outcomes in eating disorders showed that patients with concurrent ASD, elevated levels of ASD traits or ASD‐related developmental difficulties responded less successfully to treatment, compared to patients without concurrent ASD and low ASD traits, respectively (Nielsen et al ., ; Stewart, McEwen, Konstantellou, Eisler & Simic, ; Tchanturia, Larsson & Adamson, ). In SUD, conventional treatment methods might not be appropriate for patients with concurrent ASD, like for example group therapy because of deficits in social skills as well as distress and anxiety potentially evoked by group settings (Arnevik & Helverschou, ; Drake, Hank, Edwards, Ensum & Bateman, ; Rengit et al ., ).…”
Section: Introductionmentioning
confidence: 99%